CT Irradiation-induced Changes of Gene Expression within Peripheral Blood Cells. Issue 1 (July 2020) - Kaatsch, Hanns Leonhard; Majewski, Matthäus; Schrock, Gerrit; Obermair, Richard; Seidel, Jillyen; Nestler, Kai; Abend, Michael; Waldeck, Stephan; Port, Matthias; Ullmann, Reinhard; Becker, Benjamin Valentin
Abstract : Abstract: Computed tomography (CT) is a crucial element of medical imaging diagnostics. The widespread application of this technology has made CT one of the major contributors to medical radiation burden, despite the fact that doses per individual CT scan steadily decrease due to the advancement of technology. Epidemiological risk assessment of CT exposure is hampered by the fact that moderate adverse effects triggered by low doses of CT exposure are likely masked by statistical fluctuations. In light of these limitations, there is need of further insights into the biological processes induced by CT scans to complement the existing knowledge base of risk assessment. This prompted us to investigate the early transcriptomic response of ex vivo irradiated peripheral blood of three healthy individuals. Samples were irradiated employing a modern dual-source-CT-scanner with a tube voltage of 150 kV, resulting in an estimated effective dose of 9.6 mSv. RNA was isolated 1 h and 6 h after exposure, respectively, and subsequently analyzed by RNA deep sequencing. Differential gene expression analysis revealed shared upregulation of AEN, FDXR, and DDB2 6 h after exposure in all three probands. All three genes have previously been discussed as radiation responsive genes and have already been implicated in DNA damage response and cell cycle control after DNA damage. In summary, we substantiated the usefulness of AEN, FDXR, and DDB2 as RNA markers of low dose irradiation. Moreover, the upregulation of genes associated with DNA damage reminds one of the genotoxic nature of CT diagnostics even with the low doses currently applied. Abstract : Supplemental digital content is available in the text.